CO2 adsorption performance of AC and Zn-MOF for the use of carbon capture and sequestration (CCS) - Nor Khonisah, Daud (Elsevier Ltd, 2023)
The purpose of this study is to examine and compare the performance of different kinds of solid adsorbents for CO2 adsorption. The performance of selected solid adsorbents such as activated carbon (AC) and Zn-MOF in CO2 adsorption was examined and compared based on variables: impact of adsorbent dose (200–400 mg) and the initial pressure (4–20 psig). Based on the characterisation results of the FTIR, EDX and XRD analyses, the outcomes suggest that Zn-MOF and AC have been successfully developed. The SEM images show agglomerations of Zn-MOF particles whilst a smooth surface has been observed on AC. According to the TGA analysis, AC manages to keep firm compared to Zn-MOF where it does not have the ability to maintain its frame when temperature reaches above 200 °C. From the CO2 adsorption results, the findings show that Zn-MOF performs better with a high CO2 adsorption capacity relative to AC in the low-pressure system. Under optimal conditions, the CO2 adsorption of 145.1 and 79.28 mg/g of Zn-MOF and AC were achieved, respectively indicated that Zn-MOF gives a good feature for a solid adsorbent to capture a higher percentage of CO2.